Problems of informatization of higher school in the perception of subjects of the educational process - Tsvetkova, Irina Viktorovna; Bezgina, Olga Anatolevna; Evchenko, Olga Sergeevna; Gurov, Vladimir Alekseevich; Vasileva, Svetlana Yurevna (SHS web of conferences, 2021)
The relevance of the topic is due to the widespread use of information technology in higher educational institutions. This trend has conflicting and ambiguous consequences. On the one hand, the use of information technology increases the accessibility of education, makes the educational process flexible, and expands the possibilities of using visual materials. On the other hand, problems arise in the development of teaching methods that are necessary to stimulate the learning activity of students. To study the attitude of teachers and students to the problems of using information technology in higher education, the scientific publications of foreign and Russian scientists were analyzed. The purpose of the research is to study the peculiarities of perceiving the problems of informatization of the educational process by teachers and students of higher educational institutions. The empirical basis of the study was the materials of a sociological survey conducted among students of Togliatti State University in 2014 (N=359) and in 2019 (N=353). Comparative analysis of the results shows that within five years the number of students who are interested in using information resources in the educational process has significantly increased. A similar trend can be traced in the interest in using educational programs and simulators. From 2014 to 2019, the number of students who would like to receive supplementary training in information technology has doubled. The growing interest of students in the use of information technology necessitates the development of modern teaching methods, changes in the forms of interaction between students and teachers in the educational process. The solution to these problems at the present stage is associated with the search for the optimal combination of information and interactive technologies in the educational process.